PH-responsive targeted gold nanoparticles for in vivo photoacoustic imaging of tumor microenvironments. Issue 2 (2nd January 2019) - Li, Shiying; Lui, Kwok-Ho; Tsoi, Tik-Hung; Lo, Wai-Sum; Li, Xin; Hu, Xuesen; Chi-Shing Tai, William; Hiu-Ling Hung, Clara; Gu, Yan-Juan; Wong, Wing-Tak
Abstract : Stable, tumor-specific and pH-responsive gold nanoparticles are carefully designed for aggregation-induced photoacoustic in vivo imaging. Abstract : The acidic microenvironment of tumor tissues has been proven to be a major characteristic for differentiation from normal tissues, thereby providing a desirable target for both disease diagnosis and functional imaging. We herein introduce a way to endow gold nanoparticles with aggregation behaviour induced by pH tuning. The nanoparticle surface was modified with two thiol conjugate molecules, which could smartly stabilize it at the pH of blood and normal tissues but induce aggregation in response to the acidic extracellular pH in tumor. The surface conjugate molecule composition effect was studied systematically, and at the optimal surface conjugate molecule composition, a pH-responsive active tumor-targeting c(RGDyk)-MHDA/LSC@AuNP nanoprobe was successfully obtained and showed a significantly enhanced contrast effect for both in vitro and in vivo photoacoustic (PA) imaging. Intravenous administration of our nanoprobe to U87MG tumor-bearing nude mice showed PA imaging contrasts almost 3-fold higher than those for the blocking group. Quantitative biodistribution data revealed that 9.7 μg g −1 of nanoprobe accumulated in the U87MG tumor 4 h post-injection. These findings might provide an effective strategy for developing new classes of intelligent and biocompatible contrast agents with a high efficiency for PA imaging and PA imaging-guided cancer therapy.